THE INFLUENCE OF WORK ENVIRONMENT AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF STATE CIVIL APPARATUS AT THE REGIONAL SECRETARIAT OF BINJAI CITY - Achyar Rezski Pane; Nuraini; Syafruddin Ritonga (RADJA PUBLIKA, 2024)
The purpose of this study was to determine the effect of work environment and organizational culture on employee performance. This research method uses quantitative methods. The population was 110 and the sample was 110 employees with a total sampling technique. Based on the results of the t-test, there was a significant effect of the work environment on performance, which was obtained by the regression coefficient value of the Work Environment variable (t count) of 12.987 with a t table of 1.658, meaning that the t count value ˃ t table and significance of 0.000 ˂ 0.050, so that the first hypothesis was accepted. Based on the results of the t-test, there was a significant effect of organizational culture on performance, which was obtained by the regression coefficient value of the Work Environment variable (t count) of 12.987 with a t table of 1.658, meaning that the t count value ˃ t table and significance of 0.000 ˂ 0.050, so that the second hypothesis was accepted. Simultaneously there is a significant influence between the Work Environment and Organizational Culture on performance as seen from the calculated F value of 61,667 and the F table value of 3,081 with a significance of 0.000 <0.050, then it can be said that the calculated F value> F Table and significance 0.000 <0.050. In addition, the coefficient of determination (R²) = 0.309, which means that the work environment and organizational culture have a 30.9% influence on employee performance.